Growth performance and gut function of broiler chickens received barley-based diets with or without an enzyme mixture - Afifian tehrani, Ali; Hassanpour, Hossein; Karimi-Torshizi, Mohammad Amir; Akbari , Mohammad Reza; Khajali, Faribourz (Journal of Poultry Sciences and Avian Diseases, 2024)
An experimental study was performed to evaluate the responses of broiler chickens to dietary substitution of barley for corn. A total of 252 one-day-old broiler chicks were randomly distributed among 18 floor pens. Six such pens were then randomly assigned to each dietary treatment. Dietary treatments consisted of a corn-based diet, a barley-based diet, and the barley-based diet plus an enzyme mixture. Results indicated that barley substitution for corn significantly (p< 0.0001) impacted broiler performance criteria. However, enzyme supplementation significantly (p= 0.02) improved the feed conversion ratio to the extent obtained in the corn control. The villus absorptive surface area was shrunk in birds fed a barley diet compared to the corn diet. Nevertheless, supplementation of the barley diet with the enzyme mixture significantly (p= 0.02) restored the situation. The expression of the TLR2 gene was significantly down-regulated by replacing barley with corn. Enzyme supplementation of the barley diet significantly (p< 0. 001) up-regulated TLR2 gene expression but not to the extent observed in the corn control group. Significant increases were observed in circulatory levels of uric acid (p< 0.05), total protein (p